URGENSI PENDIDIKAN KEWIRAUSAHAAN BAGI LULUSAN SMK DALAM MEMASARKAN KEAHLIAN DI DUNIA KERJA - Anyjrah Narlita Isnaini (BORJUIS: JURNAL OF ECONOMY, 2024)
Vocational High School (SMK) graduates often face challenges in marketing their skills in the world of work. The high unemployment rate for vocational school graduates, intense competition, and demands for additional skills from industry indicate the need for entrepreneurship education to equip them with the ability to market themselves effectively. This article aims to examine the urgency of entrepreneurship education for vocational school graduates and propose an appropriate curriculum through literature studies of various sources such as journals, books and related reports. The study results show that entrepreneurship education is very important for developing an entrepreneurial mindset and attitude, self-marketing skills, and the ability to innovate in vocational school graduates. The recommended curriculum includes personal branding development, self- presentation, career management, introduction to entrepreneurship, and collaboration with industry. By integrating entrepreneurship education, vocational school graduates will be better prepared to compete in the world of work as employees and independent entrepreneurs. It is concluded that entrepreneurship education needs to be implemented comprehensively in vocational schools to increase graduates' competitiveness and opportunities for success in marketing their skills.